Didactic Audiovisual Translation. An Implementation of a Subtitling Task in a Classroom of Secondary Education - Goñi, Edurne; Azcona Magaña, Alba (Huarte de San Juan. Filología y Didáctica de la Lengua, 2025)
Research on the implementation of Didactic Audiovisual Translation (dat) and, more specifically, using subtitling tools in the language classroom is abundant; nevertheless, there is a dearth of studies exploring its use for acquiring grammar in Secondary Education (E.S.O.). In this study, we present the results of a project based on dat, the Subtitling News, which was implemented in a class of the second year of E.S.O. Students completed a subtitling task individually, and merged the individually subtitled pieces into one group project. After the completion of the subtitling, both groups answered a satisfaction questionnaire. The results, positive on both aspects, offer teachers insights into a new methodology to be carried out in their secondary education classes to improve grammar knowledge in a motivating way using subtitling tools.